A Third Surgically Managed Ectopic Pregnancy after Two Salpingectomies Involving the Opposite Tube - Naoyuki Iwahashi; Yoko Deguchi; Yuko Horiuchi; Kazuhiko Ino; Kenichi Furukawa (Case Reports in Obstetrics and Gynecology)
Recurrent ectopic pregnancy in a remnant fallopian tube after ipsilateral salpingectomy is clinically rare. We report the extremely rare case of a third recurrent ectopic pregnancy after two previous salpingectomy procedures involving the opposite tube. A 26-year-old woman, gravida 3 para 0, experienced three ectopic pregnancies brought about by natural conception, all of which were treated surgically (right partial salpingectomy, right remnant tube resection, and left total salpingectomy). During the two salpingectomy procedures involving the right tube, the patency of the intact left tube was intraoperatively confirmed with indigo carmine. The most appropriate surgical intervention should be discussed when managing recurrent ectopic pregnancies. It might be necessary to perform total salpingectomy to reduce the risk of future recurrence on the remaining tube.